PENGARUH ENVIRONMENTAL PERFORMANCE DAN ENVIRONMENTAL DISCLOSURE TERHADAP ECONOMIC PERFORMANCE - Danny Widarto; Rina Mudjiyanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
The aim of this research was to examine the influences of the environmental performance and environmental disclosure to the economic performance. This research focused on the public companies complying with PROPER KLH RI in the period of 2010-2012. The sample was 35 companies. The data were then analyzed using multiple linear regressions. Based on the analysis, it was proved that the environmental performance partially had significant effect to the economic performance. Meanwhile, the environmental disclosure partially had no significant effect to the economic effect. Yet, simultaneously both environmental performance and environmental disclosure influenced significantly to the economic performance, meaning the concept of environmental accounting begins to have Indonesian public acceptance. The model of environmental accounting has improved and influenced the economic performance. Keywords: environmental accounting, environmental performance, environmental disclosure, and economic performance.